4x+2(x+2)=

Simple and best practice solution for 4x+2(x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+2(x+2)= equation:


Simplifying
4x + 2(x + 2) = 0

Reorder the terms:
4x + 2(2 + x) = 0
4x + (2 * 2 + x * 2) = 0
4x + (4 + 2x) = 0

Reorder the terms:
4 + 4x + 2x = 0

Combine like terms: 4x + 2x = 6x
4 + 6x = 0

Solving
4 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 6x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 6x = 0 + -4
6x = 0 + -4

Combine like terms: 0 + -4 = -4
6x = -4

Divide each side by '6'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 11.8x=18 | | -7(1-4m)=13(3m-9) | | .7x=12 | | 2.4x=1.6 | | 3x^7+5=-6 | | 7x^9-4=12 | | (y-3)(y-2)(y-1)=3y+9 | | t^2-10t+15=0 | | 2(p+2)=1.8p-2-(p+5) | | Ln(x)=45 | | 4x+5(x-4)= | | Lnx=35 | | (y-6)(y-5)=y+43 | | 3x-20=1+26 | | 5(6x+3)=25 | | 2x+7x-18=90 | | 2.3=p+0.6 | | 9h-3h=-18 | | 15y=90+9x | | 5x+2(2x+2)= | | 9x+15y=90 | | 12=6.28r(r+5) | | 9r-7r=20 | | 8z+15=-15 | | 5x^9+4=2 | | M-3=13.8 | | -(1-10t)=-11+8t | | 2x-5=3x-15 | | 5(b+9)=5b+45 | | 4x+4(x-4)= | | 3v-2v=13 | | -10y-3-2.5y+20=67 |

Equations solver categories